EFFECT OF THE RESIUDAL OF SULFUR IN SOIL AND APPLICATION OF N,P,K FERTILIZERS ON GROWTH AND YIELD OF BREAD WHEAT - Zeboon, N. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at the fields of field Crops Dept.- Coll. of Agric.Univ. of Baghdad during winter season 2012 – 2013 . The objective of this experiment was to know the effect of the residual on of sulfur in soil and NPK fertilizers on some growth, yield components and grain yield of bread wheat Triticum aestivum L. , variety Abu – Ghraib 3. This experiment carried out , using factorial experiment within Randomized Complete Block Design with three replicats . The first variable, influence of sulfur residual from last season (0 ,2 ,4 ,6) Mg. ha-1 . The second variable, was the same quantity from NPK , which added last season and half of this quantity of the last season from NPK . The results revealed , that the residual sulfur effected significantly on some growth and yield component. The sulfer level 2 Mg ha-1 produced highest grain yield (8.494 Mg. ha-1) and biological yield (31.11 Mg. ha-1) .Using half quantity of NPK effected on some yield components but didn,t effect on grain yield and biological yield . It can be concluded that wheat plants could be useable from agriculture sulfur, which added to the wheat field at the last season with level of 2 Mg. ha-1.